Nipah Virus Disease: An Updated Review - Vandana, Karnati; Swarna, Panga; Sreevidya, Battala; Sudheer, Akkiraju; Pradeepkumar , Bhupalam; Revanth , Bandaru; Reddy , Kanala Somasekhar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The Nipah virus (NiV) is a member of the Paramyxoviridae family of zoonotic viruses that is extremely contagious and potentially fatal. The Nipah virus was first discovered in 1999 during an outbreak in Malaysia. Since then, it has periodically caused outbreaks throughout South and Southeast Asia, especially in Bangladesh and India, and it continues to be a serious public health concern. The virus is primarily transmitted to humans through direct contact with infected fruit bats, which serve as natural reservoir hosts for the Nipah virus. Human-to-human transmission can also happen when infected people's body fluids come into close contact with one another. The Nipah virus has a high death rate that varies depending on the outbreak and can cause a variety of clinical presentations, including encephalitis, severe respiratory illnesses, and asymptomatic infections. Fever, headache, dizziness, drowsiness, and confusion are common signs of Nipah virus infections, which may lead to the rapid onset of coma in the patient. The Nipah virus does not presently have a specific antiviral treatment; instead, infection control methods and supportive care are the foundation of management to stop the virus from spreading. Nipah virus outbreaks must be stopped with an approach that includes community involvement, public health education, and surveillance of both human and animal populations. Additionally, efforts are directed toward developing vaccines as a more potent form of prevention. The Nipah virus is a clear reminder of the continuous threat that newly emerging infectious diseases pose, as well as the necessity of having strong surveillance systems and quick response times in place to lessen the effects that these outbreaks have on public health.